Tindak Tutur Direktif Guru Dalam Pembelajaran Bahasa Indonesia Di Kelas XI SMA Negeri 4 Padang - Tressyalina; Ningrum, Ayunda (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to describe the form of directive speech acts of teachers in Indonesian language learning at SMA Negeri 4 Padang. This type of research is qualitative research with descriptive method. The research data used is the teacher's speech in Indonesian language learning at SMA Negeri 4 Padang. The data source of this research is Mrs. Erlin Sunarya as an Indonesian language teacher at SMA Negeri 4 Padang. The data collection technique used passive participation observation technique. Data analysis techniques are data reduction, data presentation, and conclusion drawing. The result of this research shows that there are five forms of directive speech acts, namely telling speech, begging speech, suggesting speech, demanding speech, and challenging speech. There are four forms of speech strategies, namely speaking frankly without preamble, speaking with positive politeness, speaking with negative politeness, and speaking vaguely. The dominant speech act used by teachers in Indonesian language learning is the directive speech act of telling. The dominant speech strategy is a straightforward speech strategy with positive politeness.